Too Poor for Peace? : Global Poverty, Conflict, and Security in the 21st Century - Chollet, Derek H.; Brainard, Lael (Book collections on Project MUSE., 2007)
"Investigates the complex and dynamic relationship between poverty and insecurity, exploring possible agents for change. Brings the latest lessons and intellectual framework to bear in an examination of African leadership, the private sector, and American foreign aid as vehicles for improving economic conditions and security"--Provided by publisher